2015
DOI: 10.11604/pamj.2015.22.252.6501
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of different brands of albendazole against soil transmitted helminths among students of Mendera Elementary School, Jimma, Southwest Ethiopia

Abstract: IntroductionDifferent brands Albendazole are commercially available and the efficacious brand/s is/are required for effective control of STHs infection. Thus, this study is aimed at determining the therapeutic efficacy of different brands of albendazole against soil transmitted helminths among school children of Jimma town.MethodsA cross sectional survey for prevalence of geohelminths and a randomized trial for efficacy study of different brands of albendazole was conducted among students Mendera Elementary Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…We evaluated 44 studies with an average Jadad score of 2.5 and a total of 7273 participants positive for A lumbricoides (table N in appendix 2 gives detailed numbers) to evaluate the effect of the four anthelmintic drugs against A lumbricoides (fig 1 ). Pooled estimates were based on 19 studies with only one treatment, 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 22 studies with two treatments, 12 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 and three studies with three eligible treatments. 64 65 66…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated 44 studies with an average Jadad score of 2.5 and a total of 7273 participants positive for A lumbricoides (table N in appendix 2 gives detailed numbers) to evaluate the effect of the four anthelmintic drugs against A lumbricoides (fig 1 ). Pooled estimates were based on 19 studies with only one treatment, 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 22 studies with two treatments, 12 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 and three studies with three eligible treatments. 64 65 66…”
Section: Resultsmentioning
confidence: 99%
“…For estimating the drug efficacy against hookworm, we looked at data from 7178 individuals from 38 studies (table 1 ; table N in appendix 2) with an average Jadad score of 2.8. Pooled estimates included 12 studies with one treatment, 25 26 30 31 32 34 36 38 42 43 68 21 studies with two treatments, 12 43 44 46 47 48 49 50 51 52 53 54 55 56 57 58 62 63 68 69 70 and five studies with three treatments. 64 65 66 71 72 …”
Section: Resultsmentioning
confidence: 99%
“…Respondents from sixty different households were selected using a systematic random sampling design in three different villages. The first household was selected randomly using the lottery method described in Tefera et al 24 , and thereafter every third household along a road or…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…All the three ailments viz. lethargy, anaemia and appetite loss managed with most of plants are classified as nutritional disorders by Cook 24 . Most plants are used to manage more than one disease.…”
Section: Common Ailment Categories Managed By Plant Species Among Prementioning
confidence: 99%
“…This risk reduction might be related to the improved sanitation, access to better water supply, improved personnel hygiene or the higher e cacy of the available treatments against A lumbricoides [115]. In support of this, a local study conducted on the e cacy of albendazole and mebendazole indicated that the drugs have 95% e cacy in decreasing the burden of the parasite in Ethiopia [125].…”
Section: Discussionmentioning
confidence: 99%